Penurunan Resiko Jatuh Pasien Melalui Supervisi Kepala Ruang Perawatan - Dedes Sahpitra; Sri Yulia; Renny Triwijayanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
Errors that may be made by nurses associated with the action of reducing the fall risk can be minimized, one way is by supervision. The fall risk in patients if occured can cause various impacts such as injuries, disability, and even death. The objective of this research is finding out the relationship between supervision by head nurse with reduction of fall risk in in-patient room. This research was a descriptive correlational study with cross sectional approach. The number of samples was 49 nurses. This study used chi-square test. Data were gathered by means of questionnaires, supervision by head nurse, and reduction of fall risk. The result showed that there was relationship between supervision by head nurse with reduction of the fall risk with Ï value = 0,015Â (Ï value Î± < 0,05). There was a relationship between supervision by head nurse with reduction of risk of falling. It is necessary to do a periodic evaluation in reducing the fall risk through supervision and making a standard guideline for supervision about fall risk.